PENERAPAN MUSIK DIATONIS MINOR UNTUK MEWUJUDKAN SUASANA SUNYI DAN SENDU PADA FILM “SENANG BERTEMU DENGANMU” - I Made Suhartana; I Kadek Puriartha; I Made Denny Chrisna Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
“Senang Bertemu Denganmu” is a fictional film that tells the story of Mega, a young man who found out a mysterious diary in his mother's inherited house. Gradually. In films, sound can liven up the atmosphere to create the feeling of sadness, joy, anger and fear. In general, the sound in films consists of two types, namely diegetic sound and non-diegetic sound which includes dialogue, sound effects and music. One of the types of musical scale that can cause a quiet and sad atmosphere is a minor diatonic. The minor diatonic is music that uses seven basic notes, namely la, si, do, re, mi, fa, sol, and la. Music with minor diatonic scales can create a quiet and sad atmosphere, based on the theory of diegetic sound which is all the elements of sound in the film, including dialogue, sound effects and ambiance. Diegetic sound helps to create the quiet and sad atmosphere that occurs in the film “Senang Bertemu Denganmu”. The results of the diegetic sound theory can provide a more detailed sound through the foley technique so that after all the elements of the diegetic sound are combined with the accompaniment of minor diatonic music combined with the strains of a piano, the quiet and sad atmosphere in the film “Senang Bertemu Denganmu” can be realized. Therefore, it can convey an impression and message to the audience.